THE INFLUENCE OF TRAINING METHOD AND MUSCLE CONSTRUCTION TOWARDS TAEKWONDO KICK CAPABILITY - Jonas Solissa (EDU SCIENCES JOURNAL, 2020)
This study aims to determine the effect of circuit training methods and interval training methods on the ability of the Taekwondo Round-House kick. The study was carried out at Unpatti Taekwondo athletes in Ambon 2019, using an experimental method with 2 x 2 factorial design. Data were analyzed using Variant Analysis (ANOVA).The results showed, that: (1) Overall there was a difference in the ability of Taekwondo Round-House kick between the circuit training method and the interval training method, (2) For taekwondoin who had high muscle flexibility, the interval training method was better than the circuit training method for Taekwondo Round-House Kick ability, (3) For taekwondoin which has low muscle flexibility, there is no significant difference between the circuit training method and the interval training method for Taekwondo Round-House kick capability. (4) There is an interaction between the training methods with the flexibility of the Taekwondo dolyo kick ability